Space tourism - Budnikova, Anna (My University, 2014)
Tourism is important and, in some cases, vital for many countries. The travel and tourism industry has grown and developed into one of the largest businesses in the world. One of the most interesting types of traveling is space tourism.
Keywords: space tourism; travel; tourism; космічний туризм; подорож; туризм; космический туризм; путешествие